Kerjasama Sekolah dan Orangtua dalam Pembinaan Akhlak Siswa - Amalia Rizki Febrianti; Asep Dudi Suhardini; Fitroh Hayati (Bandung Conference Series: Islamic Education, 2022)
Abstract. This research was conducted to find out the description of the cooperation carried out by schools and parents in fostering the morals of students at Mdt. Al-Ikhlas in Gandasari Village, a description of the morals of students in increasing cognitive insight, appreciation of affective values and behavioral habits in moral development. The approach used is a qualitative approach with the type of case study research. This research was conducted at Gandasari Village with informants from this study the Principal and Teachers and Parents. Data collection techniques in this study used interviews and questionnaires. Data analysis includes steps of data reduction, data presentation and drawing conclusions. Test the validity of the data using triangulation. The results of the study of School and Parent Cooperation in Moral Development shows that: 1. Cooperation between schools and parents in fostering the morals of students in the cognitive domain goes well because the teacher carries out his responsibilities and roles in school well and parents do the same thing where the learning that children get at school is repeated continuously by parents at home. 2. Cooperation between schools and parents in fostering students' morals in the affective domain can be indicated through the development of discipline in studying a learning material. Schools encourage students to be responsible for completing the material provided and parents have more roles to encourage children to understand the material taught at school. 3. cooperation between schools and parents in the psychomotor domain is to encourage children to develop skills in completing work related to motor activities. This is obtained through training and habituation carried out by teachers and parents. Abstrak. Penelitian ini dilakukan untuk mengetahui gambaran kerjasama yang dilakukan sekolah dan orangtua dalam pembinaan akhlak sisw di Mdt. Al-Ikhlas Desa Gandasari, gambaran akhlak peserta didik dalam meningkatkan wawasan kognitif, penghayatan nilai afektif dan kebiasaan berperilaku dalam pembinaan akhlak. Pendekatan yang digunakan adalah pendekatan kualitatif dengan jenis penelitian studi kasus. Penelitian ini dilakukan di Desa Gandasari dengan informan dari penelitian ini adalah Kepala Sekolah dan Guru serta Orangtua. Teknik pengumpulan data pada penelitian ini menggunakan wawancara dan kuesioner. Analisis data meliputi langkah reduksi data, penyajian data dan penarikan kesimpulan. Uji keabsahan data menggunakan triangulasi. Hasil penelitian Kerjasama Sekolah dan Orangtua dalam Pembinaan Akhlak siswa menunjukan bahwa: 1. Kerjasama sekolah dan orangtua dalam pembinaan akhlak siswa di pada ranah kognitif berjalan dengan baik karena guru melaksanakan tanggung jawab dan perannya disekolah dengan baik dan orangtua pun melakukan hal yang sama yang mana pembelajaran yang didapatkan anak disekolah diulang kembali secara kontinyu oleh orangtua dirumah. 2. Kerjasama sekolah dan orangtua dalam pembinaan akhlak siswa pada ranah afektif dapat diindikasikan melalui pembinaan kedisplinan dalam mempelajari suatu materi pembelajaran. Sekolah mendorong siswa untuk bertanggung jawab dalam menyelesaikan materi yang diberikan dan orangtua memiliki peran yang lebih untuk mendorong anak dalam memahami materi yang diajarkan disekolah. 3. kerjasama sekolah dan orangtua pada ranah psikomotorik adalah mendorong anak dalam memunculkan keterampilan dalam menyelesaikan suatu pekerjaan yang berhubungan dengan aktivitas motoric. Hal ini didapat melalui latihan dan pembiasaan yang dilakukan oleh guru dan orangtua.